EFFECT OF LOAD, ROTATION SPEED AND SLIP RATIO ON THE WEAR BEHAVIOUR OF PVD-COATED HOTVAR STEEL UNDER LUBRICATING CONDITIONS - Gercekcioglu, E.; Dagasan, E.; Kaleli, H.; Tugral, F. A. (SCIBULCOM LTD, 2012)
In this study, the effect of load and rotation speed on wear behaviour of the HOT VAR (hot work) steel was investigated under lubricated abrasive conditions. The specimens were coated! with titanium nitride (TiN) by physical vapour deposition (PVD) method on a small part of the heat-treated surface. Coating method was only applied to the ridge parts of the HOT VAR steel specimens. Average thickness of the TiN layer was determined as 1.89 mu m. Disc disc configuration was used during the wear tests. To determine the effect of load and rotation speed, the tests were carried out in 4 different loads and rotation speeds. As a result, it was observed that the mass loss values of the heat-treated specimen increase more than of the coated specimens, because there is an increasing effect of coating process on the hardness value of the specimens as the load increases. Similar to these mass loss results, roughness average (Ra) values of both specimens are close to each other in initial low load values, but later on the load value of 125 N, partial increases are observed. When the load increases to 175 N, Ra values of both specimens decrease and become similar. This is well explained by depletion of TiN layer during abrasive wear.
Keywords: PVD coating; nitriding; disc-disc wearing; abrasive wear; lubrication; DUPLEX COATINGS; IMPROVEMENT; Engineering